Projection Stereolithographic Fabrication of Human Adipose Stem Cell-Incorporated Biodegradable Scaffolds for Cartilage Tissue Engineering - Sun, Aaron X.; Lin, Hang; Beck, Angela M.; Kilroy, Evan J.; Tuan, Rocky S. (Frontiers in Bioengineering and Biotechnology, 2015)
The poor self-healing ability of cartilage necessitates the development of methods for cartilage regeneration. Scaffold construction with live stem cell incorporation and subsequent differentiation presents a promising route. Projection stereolithography (PSL) offers high resolution and processing speed as well as the ability to fabricate scaffolds that precisely fit the anatomy of cartilage defects using medical imaging as the design template. We report here the use of a visible-light-based PSL (VL-PSL) system to encapsulate human adipose-derived stem cells (hASCs) into a biodegradable polymer [poly-d,l-lactic acid/polyethylene glycol/poly-d,l-lactic acid (PDLLA-PEG)]/hyaluronic acid (HA) matrix to produce live cell constructs with customized architectures. After fabrication, hASCs showed high viability (84%) and were uniformly distributed throughout the constructs, which possessed high mechanical properties with a compressive modulus of 780 kPa. The hASC-seeded constructs were then cultured in control or TGF-β3-containing chondrogenic medium for up to 28 days. In chondrogenic medium-treated group (TGF-β3 group), hASCs maintained 77% viability and expressed chondrogenic genes Sox9, collagen type II, and aggrecan at 11, 232, and 2.29 × 105 fold increases, respectively compared to levels at day 0 in non-chondrogenic medium. The TGF-β3 group also produced a collagen type II and glycosaminoglycan-rich extracellular matrix, detected by immunohistochemistry, Alcian blue staining, and Safranin O staining suggesting robust chondrogenesis within the scaffold. Without chondroinductive addition (Control group), cell viability decreased with time (65% at 28 days) and showed poor cartilage matrix deposition. After 28 days, mechanical strength of the TGF-β3 group remained high at 240 kPa. Thus, the PSL and PDLLA-PEG/HA-based fabrication method using adult stem cells is a promising approach in producing mechanically competent engineered cartilage for joint cartilage resurfacing.